Empowerment of Santri through Health Cadre Training and Peer Counseling Programs to Address Academic Stress in Islamic Boarding Schools - Zamzam, Maki Zamzam; Herdiani, Novera; Lubis, Clarissa Alfiyah; Mazayah, Elinatul (Journal of Health Community Service, 2025)
Academic stress is a significant issue frequently experienced by students (santri) in Islamic boarding schools (pesantren) due to high academic demands, busy schedules, and limited access to mental health support, all of which negatively impact their learning motivation, as well as physical and mental health. This community service program aimed to enhance students' understanding of academic stress, empower them as mental health cadres, develop a peer counseling system, and equip them with stress management skills. The program was conducted at Pondok Pesantren Burhanul Hidayah Sidoarjo, involving 14 Santri Husada cadres through two main stages: education on academic stress and training in peer counseling. Education was delivered through seminars, discussions, and distribution of printed and digital materials, while training included lectures, group discussions, role simulations, and practical peer counseling sessions. Evaluation was carried out using pre- and post-tests, as well as observation of counseling skills. The results showed an improvement in students' knowledge, with the average score increasing from 90 to 94 after intervention, along with the establishment of peer counseling groups that provided internal support. Furthermore, students became more skilled in applying basic stress management techniques such as relaxation and time management. These findings indicate that education and peer counseling training are effective in enhancing students' capacity to cope with academic pressure. In conclusion, empowering students through peer counseling represents a sustainable strategy for strengthening mental health support in Islamic boarding schools, and wider, routine implementation is recommended to improve students’ resilience in facing academic challenges.